Bronchial asthma with systemic sclerosis – a case study - Czarny-Działak, Małgorzata A.; Głuszek-Osuch, Martyna; Wiraszka, Grażyna R. (Medical Studies/Studia Medyczne, 2016)
Asthma affects from 1% to 18% of people depending on the country, and systemic sclerosis affects 0.025%. Asthma is a chronic inflammatory disease of the respiratory tract. Inflammation is induced by a plurality of cells and their release of mediators. Systemic sclerosis is a connective tissue disease belonging to the so-called major systemic diseases characterised by vascular damage, immune disorders, and excessive accumulation of extracellular matrix components in various internal organs and skin. As the disease progresses, they lead to multi-organ failure, and eventually death of the patient. It was formerly thought that there was no connection between diseases within the circle of allergies and autoimmunology. Currently, it is assumed that the cause of both disease groups is a disorder of the immune system. An example of this type of relationship is described in our clinical case where in one patient bronchial asthma coexists with systemic sclerosis.